Microwave-Assisted Efficient and Chemoselective Acetalization of Aldehydes with Trimethyl Orthoformate (Journal of Sciences, Islamic Republic of Iran)
Efficient and chemoselective protection of aldehydes to the corresponding dimethyl acetals have been carried out by mixture of trimethyl orthoformate and methanol in the presence of a catalytic amount of TMSCl or AlCl3 under microwave irradiation. Under these conditions, acetalization of ketones does not take place and they remain intact under reaction conditions. The results are compared with the reaction of an aldehyde with trimethyl orthoformate in the presence of a mild Lewis acid.